HIPPOTHERAPY OF CHILDREN WITH DOWN SYNDROME: DIFFICULTIES, RECOMMENDATIONS FOR WORK - Czerw, Monika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
There are many forms of therapy for children with Down syndrome. Among them, hippotherapy is gaining more and more scientific recognition in Poland. Hippotherapy represents an alternative form of rehabilitation, with a key link being an adequately trained horse. The major benefit of hippotherapy is a broad spectrum of effect. It is important for the rehabilitation of people with Down syndrome that hippotherapy offers great opportunities to stimulate physical, cognitive, sensory and verbal areas. Its effect on social functioning of the individual is also substantial. Attractive forms of the therapeutic sessions, positive results of hippotherapeutic effects and the increasing popularity represent the motivation for both practitioners and scholars for organization of knowledge and limitation of scepticism about this field of science.This paper presents author’s observations collected over many years of work as a hippotherapist with people with disabilities. It is aimed to bring closer the aspect of using hippotherapy in the work with children with Down syndrome. The paper also stresses the difficulties and methods to overcome them. It identifies the risks and the observed successes.